Comprehensive analysis of molecular markers linked to antimalarial drug resistance in Plasmodium falciparum in Northern, Northeastern and Eastern Uganda - Peter Olupot-Olupot; George Paasi; Thomas Katairo; Jimmy Patrick Alunyo; Alice Nakiyemba; Gilbert Gilibrays Ocen; Stephen Pande; Florance Alaroker; William Okiror; Emmaluel Ocen; Alex Oula; Charles Benard Okalebo; et al. (Malaria Journal)
Abstract Background In Uganda, antimalarial resistance in Plasmodium falciparum poses serious public health and treatment challenges. Globally, recent data have highlighted the roles of following genes in malaria resistance: Plasmodium falciparum dihydrofolate reductase (Pfdhfr), Plasmodium falciparum dihydropteroate synthetase (Pfdhps), Plasmodium falciparum chloroquine resistance transporter (Pfcrt), Plasmodium falciparum multidrug resistance gene 1 (Pfmdr1), and Plasmodium falciparum K13 propeller domain (Pfk13). This study investigated the prevalence and characteristics of P. falciparum molecular markers linked to antimalarial resistance in Northern, Northeastern, and Eastern Uganda. Methods This cross-sectional study collected 200 dried blood samples from children (2 months to 12 years) in Northern, Eastern, and Northeastern Uganda. Samples were from malaria-positive cases confirmed by rapid diagnostic tests and microscopy. Genomic DNA was extracted from these samples and analysed using Molecular Inversion Probes to detect Plasmodium falciparum genetic mutations. The sequencing was performed on the Illumina MiSeq platform, and raw data was organized and analysed with MIPTools software. Results The study sequenced over 50% of the samples at each site as follows: Apac 87.7% (43/49), Moroto 68.0% (34/50), Soroti 65.0% (13/20) and Mbale 53.1% (43/81). The Pfk13 A675V and C469Y mutations varied from 0 to 23.3% and 8.3–14.3%, in four sites, with consistently low prevalence in Apac. The Pfdhfr N51I and S108N mutations were fixed in all districts, while C59R was fixed in Moroto and nearing fixation (92–97%) in other regions. The emerging I164L mutation ranged from 1 to 10% in all sites. The Pfdhps A437G and K540E mutations were fixed in Soroti, with 3–5% wild-type prevalence in other sites. The A581G mutation showed 2.3% mixed genotypes in Mbale only. The Pfcrt K76T was predominantly wild type, except for 5% mutants in Mbale and Moroto. The pfmdr1 N86Y were wild type across all districts, except for 15% mixed genotypes in Soroti. Conclusion This study reveal rising partial artemisinin resistance and widespread antifolate resistance surpassing WHO thresholds in Northern, Northeastern, and Eastern Uganda. Emerging super-resistant parasites pose a serious threat to malaria control, necessitating urgent enhanced surveillance and alternative treatment strategies.